(untitled) (Raparin Journal of Humanities (RJH), 2021)
Agriculture Geography is one of the economic Geography branches, agriculture is considered one of the important things that attracted the human attention since their existence which was the cause of the human civilization. Agriculture Geography study the natural phenomena, water, air, soil, and vegetation that cover the earth surface, which is considered as a principle of agriculture production and it may differ from location to another, the agricultural production is a function of the human activities. Knowing the agricultural principles is considered as approve of having human activities within the human geography. This research aims at carrying out an agricultural geography analysis to check the environmental suitability of Pshdar District in producing rice, the investigation has been done in the period 2015 to 2020. The study has been made on the main resource of food that is consumed by the residents of this district. Many maps and tables have been used in this research with the aid of numerous references in order to come up with some recommendations, we have concluded that the study area is rich of human and natural resources which can become a very suitable location for rice production if it is paid some attention.